Pengaruh Variasi Sudut Elektroda Dan Kuat Arus Polaritas Terbalik Terhadap Hasil Pengelasan Shielded Metal Arc Welding - Sistro Maldini Sihombing; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study aims to obtain optimum welding results on low carbon steel with variations in electrode angle and reverse polarity direct current welding current with SMAW welding machine with adaptive sliding system two axis with speed control. Welding is done automatically and the welding speed is adjusted using the Speed Control. The method used is experimental by varying the electrode angle of 45°, 70°, 90° and the welding current strength of 90 A, 100 A, 120 A in order to determine the optimization of the welding results from the SMAW welding machine using a sliding adaptive two axis system with speed control. From the results of tests carried out with reverse polarity, the stressed tensile strength is obtained at an angle of 70° with a current strength of 100 A and for the lowest tensile strength test, namely at a letrode angle of 45° with a current strength of 100 A. Keywords: Sliding Adaptive Two Axis With Speed Control, Direct Current Reverse Polarity, Electrode Angle, Strong Current